Analisis Teknik Supervisi Pendidikan - Yuli Eka Firsanti; Muhammad Hanif; Ali Muhdi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Educational supervision is one of the strategic management functions in efforts to improve the quality of learning in educational units. This article aims to comprehensively analyze various supervision techniques used by educational supervisors, including direct supervision and indirect supervision techniques. The study was conducted through a systematic literature review approach by analyzing various relevant primary and secondary sources. The results of the analysis show that the effectiveness of supervision is highly dependent on the accuracy of technique selection based on context, teacher characteristics, and the goals to be achieved. The main techniques discussed include: classroom observation, individual interviews, inter-class visits, group meetings, workshops, teaching demonstrations, and clinical supervision. The findings of this study affirm that effective supervisors need to master a diverse repertoire of techniques and apply them adaptively. Practical and theoretical implications are discussed in the context of developing supervisor competencies and continuously improving educational quality.